Finite Temperature Properties of Clusters by Replica Exchange Metadynamics: The Water Nonamer. (Journal of the American Chemical Society, 2011)
The article presents a research which examines the thermal properties of classical nanoclusters by using replica exchange metadynamics method. It is reported that, the method is basically a sampling technique in which yields the true free energy of each relevant cluster structure. It is reported that, the researchers used water nonamer (HO), and after using the method they discovered that the nanomer second relevant structure possesses a higher configurational entropy than the first.